Malignant Peripheral Nerve Sheath Tumor in Cowden Syndrome: A First Report. Issue 4 (April 2015) - Taylor, Amy; Delon, Isabelle; Allinson, Kieren; Trotman, Jamie; Liu, Hongxiang; Abbs, Stephen; Tischkowitz, Marc
Abstract : Abstract: Malignant peripheral nerve sheath tumor is a rare malignancy, accounting for 3% to 10% of all soft-tissue sarcomas. We describe a previously healthy 48-year-old man who was diagnosed as having a high-grade malignant neoplasm involving the facial nerve in the right petrous canal after a 4-year history of deafness. The tumor was resected; histologic appearance and immunophenotype, including patchy but strong positivity for S100 protein, indicated a diagnosis of malignant peripheral nerve sheath tumor. A PTEN mutation, c.1003C >T p.(Arg335Ter), was subsequently identified as the cause of Cowden syndrome in another family member (a nephew) with dysplastic gangliocytoma of the cerebellum (Lhermitte-Duclos disease), and genetic testing in the proband's daughter indicated that he was an obligate carrier of the mutation. Sequencing of the tumor showed homozygosity for c.1003C>T, confirming the presence of a germline mutation and implying loss of the second allele. With the exception of Lhermitte-Duclos disease, tumors of the nervous system are not a prominent feature of Cowden syndrome, and this is the first report of malignant peripheral nerve sheath tumor in Cowden syndrome. Sequencing results in the tumor lend evidence to PTEN gene inactivation being implicated in tumorigenesis in this case, suggesting causality rather than chance association.